Total knee and hip replacement in rheumatoid arthritis: A current trend - V. N. Khlaboshchina; А. Е. Karateev; Е. Yu. Polishchuk; М. A. Makarov (Научно-практическая ревматология)
Total joint replacement (TJR) is a surgical procedure widely used in severe destructive joint damage. TJR of the knee and hip joint (TKR and THR respectively) occupies an important place in the complex treatment of rheumatoid arthritis (RA) and osteoarthritis (OA), and can significantly reduce pain and improve function in patients with severe structural joint damage due to an ineffectiveness of conservative therapy. In recent years, due to the development of the modern concept of active treatment of RA (treat-to-target) and the introduction of new classes of anti-inflammatory drugs, such as biologic disease modifying antirheumatic drugs and JAK inhibitors, the need for TJR in RA has begun to decrease. At the same time, the aging of the population, the increase in the number of patients with OA and the lack of generally approved pathogenetic therapy determine the increase of TKR/THR incidence in this disease. This review presents the long-term dynamics of the incidence of TKR and THR according to the national registers of different countries. The issues of the complication risks in patients with RA and OA, current recommendations for anti-rheumatic therapy in RA in the perioperative period are also considered.